Design and implication of GUI for a software CAD - Sun, Dongyu. (2008)
This dissertation project focuses on the design and implementation of the GUI for the prototype system to aid the transformation of functional models into 00 design and implementation. It looks into ways and means to design the GUI that can facilitate the required transformation and also consistent with the natural work flows carried out by analysts and designers. Prototype GUI is developed and case studies are conducted to validate the proposed design.